The fair use doctrine in the digital age: Reassessing the balance between creators' rights and public access - Marina Ramadhani (Institute Of computer Science (IOCS), 2024)
This paper critically reassesses the application and efficacy of the Fair Use doctrine within the contemporary Digital Age, noting that the rise of generative AI and mass digitization has amplified friction between Creator's Rights and the need for Public Access. This study employs a normative legal research methodology, integrating doctrinal analysis with critical policy evaluation by focusing on U.S. statutory provisions and analyzing landmark rulings concerning Digital Copyright. The main finding is that the conventional, four-factor balancing test is frequently inadequate in assessing modern cases, particularly those involving Transformation Use, as it fails to provide predictable standards. The academic contribution is the proposal of a refined analytical framework for the doctrine, aiming to re-establish the crucial balance between adequately compensating creators while actively fostering innovation and robust Public Access in an increasingly digitized information environment.